Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Kepuasan Konsumen Belanja Kebutuhan Di Grosir Sembako Ibu Ervina Kelurahan Aek Paing Tengah - Elvi Rahma Dani; Hayanuddin Safri Safri; Raja Saul Marto Hendry (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of Product Quality, Price and Price Discounts on Consumer Satisfaction shopping needs at Wholesale Sembako Mrs. Ervina Kelurahan Aek Paing Tengah To determine the effect of Product Quality, Price and Promotion on Consumer Satisfaction with a sample of 134 people. The data collection technique was carried out by questionnaire or primary data ... The results showed that simultaneously the variables of the Effect of Product Quality, Price, and Promotion had a positive and significant effect on Customer Satisfaction with a calculated F value of 11,650 greater than Ftable 2.37 with a significant value of 0.000 <0.05, partially Product Quality has a positive but insignificant effect on Customer Satisfaction obtained tcount value 0, 263 is smaller than the t table 1.65 partially Price has a positive but insignificant effect on consumer decisions to buy with t count 1.985 greater than the t table 1.65 and the significance value of t is 0.049 < 0.05, partially Promotion has a positive and significant effect on consumer decisions obtained tcount 3.317> t table 1.65 and the significance value of t is 0.001 < 0.05. Keywords: Product Quality, Price, Promotion, Consumer Satisfaction